Artificial Intelligence and University Education: Bibliometric Analysis of Research Trends and Perspectives - Elharbaoui, Elassaad; Ntebutse, Jean Gabin (Canadian Journal of Learning and Technology, 2025)
This study examines the trends and developments in publications, as well as the dynamics of scientific collaboration among authors, countries, organizations, and recent sources related to the use of artificial intelligence (AI) in university education and learning. A bibliometric analysis of 285 articles published since 2014 until March 26, 2024, drawn from the Web of Science database, revealed a strong association between AI and themes such as education, student motivation, feedback, and self-control. China and the United States are the most influential countries in this research field, with increasing collaboration from other countries such as Brazil, Canada, Israel, Poland, Singapore, South Africa, and Vietnam since 2023. The earliest publications date back to 2022 in specialized journals such as International Journal of Educational Technology in Higher Education and Educational Technology & Society. Although the analysis has limitations, such as a limited understanding of trends, partial coverage of publications, and low representativeness of data, it provides valuable insights for future interdisciplinary collaboration projects and qualitative research aimed at better understanding the dynamics of AI integration in higher education.